THE SYSTEM OF INFORMATION MANAGEMENT AS THE KEY COMPONENT FOR EFFECTIVENESS INCREASE OF THE STATE REGULATION OF INSTITUTIONAL CHANGES - Zhelizko, Oleksii Oleksandrovych (ІННОВАЦІЙНА ЕКОНОМІКА, 2020)
Желізко О.О. СИСТЕМА ІНФОРМАЦІЙНОГО ЗАБЕЗПЕЧЕННЯ ЯК КЛЮЧОВА СКЛАДОВА ПІДВИЩЕННЯ РЕЗУЛЬТАТИВНОСТІ ДЕРЖАВНОГО РЕГУЛЮВАННЯ ІНСТИТУЦІОНАЛЬНИХ ЗМІНМета. Розробка та запровадження системи інформаційного забезпечення в межах підвищення результативності державного регулювання інституціональних змін у контексті управління економічною безпекою підприємництва та національною системою економічної безпеки підприємництва в Україні.Методика дослідження. В межах дослідження використано методи: аналізу та синтезу для виявлення проблем інформаційного забезпечення державного регулювання інституціональних змін в Україні; індукції та дедукції для формування та характеристики системи інформаційного забезпечення державного регулювання інституціональних змін в країні; графічний для подання відповідної інформації.Результати дослідження. У науковій статті вказано на низьку результативність державного регулювання інституціональних змін в Україні. Відзначено, що таке положення справ негативно впливає на економічну безпеку підприємництва та функціонування національної системи економічної безпеки підприємництва в країні. Окремо досліджено взаємозв’язок між економічністю, якістю, ефективністю та результативністю державного регулювання інституціональних змін. В якості напрямку підвищення результативності державного регулювання інституціональних змін в Україні запропоновано використовувати відповідну систему інформаційного забезпечення. В межах формування та функціонування розробленої і запропонованої системи пропонується використовувати відповідний механізм.Наукова новизна результатів дослідження. У роботі дістало подальшого розвитку визначення взаємозв’язку між економічністю, якістю, ефективністю та результативністю державного регулювання інституціональних змін, яке, на відміну від існуючих, направлено на забезпечення відповідного рівня економічної безпеки підприємництва та належного функціонування СЕБП в країні. Також у дослідженні удосконалено систему інформаційного забезпечення державного регулювання інституціональних змін, яка, на відміну від існуючих, базується на відповідному механізмі її формування.Практична цінність результатів дослідження. Результати наукового дослідження можливо використати для підвищення результативності державного регулювання інституціональних змін у контексті управління економічною безпекою підприємництва та національною системою економічної безпеки підприємництва в Україні.Ключові слова: державне регулювання; економічна безпека підприємництва; економічність; ефективність; інституціональні зміни; інформаційне забезпечення; механізм; результативність; система; якість. Желизко А.А. СИСТЕМА ИНФОРМАЦИОННОГО ОБЕСПЕЧЕНИЯ КАК КЛЮЧЕВАЯ СОСТАВЛЯЮЩАЯ ПОВЫШЕНИЯ РЕЗУЛЬТАТИВНОСТИ ГОСУДАРСТВЕННОГО РЕГУЛИРОВАНИЯ ИНСТИТУЦИОНАЛЬНЫХ ИЗМЕНЕНИЙ Цель. Разработка и внедрение системы информационного обеспечения в рамках повышения результативности государственного регулирования институциональных изменений в контексте управления экономической безопасностью предпринимательства и национальной системой экономической безопасности предпринимательства в Украине.Методика исследования. В рамках исследования использовано методы: анализа и синтеза для выявления проблем информационного обеспечения государственного регулирования институциональных изменений в Украине; индукции и дедукции для формирования и характеристики системы информационного обеспечения государственного регулирования институциональных изменений в стране; графический для подачи соответствующей информации.Результаты исследования. В научной статье указано на низкую результативность государственного регулирования институциональных изменений в Украине. Отмечено, что такое положение дел негативно влияет на экономическую безопасность предпринимательства и функционирование национальной системы экономической безопасности предпринимательства в стране. Отдельно исследована взаимосвязь между экономичностью, качеством, эффективностью и результативностью государственного регулирования институциональных изменений. В качестве направления повышения результативности государственного регулирования институциональных изменений в Украине предложено использовать соответствующую систему информационного обеспечения. В рамках формирования и функционирования разработанной, а также предложенной системы предлагается использовать соответствующий механизм.Научная новизна результатов исследования. В работе получило дальнейшее развитие определение взаимосвязи между экономичностью, качеством, эффективностью и результативностью государственного регулирования институциональных изменений, которое, в отличие от существующих, направлено на обеспечение соответствующего уровня экономической безопасности предпринимательства и надлежащего функционирования СЭБП в стране. Также в исследовании усовершенствована система информационного обеспечения государственного регулирования институциональных изменений, которая, в отличие от существующих, базируется на соответствующем механизме ее формирования.Практическая ценность результатов исследования. Результаты научного исследования возможно использовать для повышения результативности государственного регулирования институциональных изменений в контексте управления экономической безопасностью предпринимательства и национальной системой экономической безопасности предпринимательства в Украине.Ключевые слова: государственное регулирование; экономическая безопасность предпринимательства; экономичность; эффективность; институциональные изменения; информационное обеспечение; механизм; результативность; система; качество. Zhelizko O.O. THE SYSTEM OF INFORMATION MANAGEMENT AS THE KEY COMPONENT FOR EFFECTIVENESS INCREASE OF THE STATE REGULATION OF INSTITUTIONAL CHANGESPurpose. The aim of the article is to develop and implement the system of information management within the effectiveness increase of the state regulation of institutional changes in the context of management of economic security of entrepreneurship and the national system of economic security of entrepreneurship in Ukraine.Methodology of research. Within the research the following methods have been used: analysis and synthesis – to detect problems of information management of the state regulation of institutional changes in Ukraine; induction and deduction – to create and provide features of the system of information management of the state regulation of institutional changes in the country; graphical – to provide the appropriate information.Findings. The scientific article has identified the low level of performance of the state regulation of institutional changes in Ukraine. It has also been stated that such a situation adversely affects economic security of entrepreneurship and functioning of the national system of economic security of entrepreneurship in the country. Separately, the relationship between cost-efficiency, quality, effectiveness and performance of the state regulation of institutional changes has been studied. To use an appropriate system of information management is suggested as one of the ways to increase performance of the state regulation of institutional changes in Ukraine. Within the formation and operation of the system developed and introduced, the data obtained in the paper have suggested using the appropriate mechanism.Originality. The research has further developed the detection of relationship between cost-efficiency, quality, effectiveness and performance of the state regulation of institutional changes, which unlike existed ones is aimed at provision of the appropriate level of economic security of entrepreneurship and the appropriate operation of SESE in the country. In addition, the research has improved the system of information management of the state regulation of institutional changes, which in contrast to the current ones is based on the appropriate mechanism of its formation.Practical value. The results of scientific research can be used to increase the performance of the state regulation of institutional changes in the context of economic security of entrepreneurship management as well as management of the national system of economic security of entrepreneurship in Ukraine.Key words: state regulation; economic security of entrepreneurship; cost-efficiency; effectiveness; institutional changes; information management; mechanism; performance; system; quality.
Keywords: Key words; state regulation; economic security of entrepreneurship; cost-efficiency; effectiveness; institutional changes; information management; mechanism; performance; system; quality.